Application of Accounting Information System for Cash Receipts and Disbursements to Improve Internal Control: Penerapan Sistem Informasi Akuntansi Penerimaan dan Pengeluaran Kas Untuk Meningkatkan Pengendalian Internal - Agustin, Ririn Silvia; Rahayu, Duwi (Universitas Muhammadiyah Sidoarjo, 2022)
This research uses descriptive qualitative method with primary and secondary data sources. Sources of data obtained through interviews, observation and documentation. The results of the study stated that the application of accounting information systems at SMA Muhammadiyah 3 reinforcement had used a system designed by the school itself, this system was called SIA SMAMUGA. The cash receipt system at SMA Muhammadiyah 3 Reinforcement comes from cash receipts and transfers. The procedure for implementing the cash receipt system has been going well, the staff just needs to log in through the application and then input data according to the receipt. The cash disbursement system at SMA Muhammadiyah 3 Tulangan comes from cash disbursements, transfers and checks. The procedure for implementing the cash disbursement system has been going well, the staff just needs to log in through the application and then input the data according to the receipt, this makes it easier to check the data that has been inputted and stored in the system. This system facilitates financial work, especially in cash disbursement. The element of internal control in the application of the cash receipts accounting information system was found to have several weaknesses including the presence of other empty sections so that there were still holding concurrent positions, namely the treasurer who doubled as cash receipts administration staff. The element of control in the application of the accounting information system for cash receipts and disbursements also has weaknesses, namely lack of supervision from the principal.